Adsorption of Cobalt Ions by Activated Carbon Prepared from Agricultural Waste Residues and Treated with Magnetic Nanomaterials: A Review: Adsorpsi Ion Kobalt oleh Karbon Aktif yang Dipreparasi dari Residu Limbah Pertanian dan Diolah dengan Nanomaterial Magnetik: Sebuah Tinjauan - Aliwi , Heba Mohammed; Halboos, Mohanad Hazim (Procedia of Engineering and Life Science, 2024)
General Background: The study of heavy metal adsorption is crucial for environmental protection and industrial wastewater management. Specific Background: The adsorption of cobalt ions (Co2+) by activated carbon derived from agricultural waste, enhanced with magnetic nanomaterials, has garnered significant interest due to its potential for cost-effective and efficient wastewater treatment. Knowledge Gap: Despite numerous studies, there remains a lack of comprehensive research on the specific combination of agricultural waste-derived activated carbon and magnetic nanomaterials for Co2+ adsorption. Aims: This study aims to meticulously review the existing literature on the preparation of activated carbon from agricultural residues, the enhancement of its properties with magnetic nanomaterials, and its effectiveness in Co2+ ion adsorption. Results: The review demonstrates that activated carbon with a large specific surface area and diverse functional groups significantly improves Co2+ adsorption. The incorporation of magnetic nanomaterials further enhances this efficiency due to increased surface area and magnetic properties. Novelty: This research uniquely combines agricultural waste valorization with advanced nanotechnology, presenting a sustainable and innovative approach to heavy metal adsorption. Implications: The findings underscore the dual environmental benefits of recycling agricultural waste and mitigating industrial pollution, offering a cost-effective and efficient solution for cobalt ion recovery from wastewater. This study serves as a valuable resource for researchers and engineers focusing on sustainable environmental remediation technologies. Highlights: Enhanced Adsorption: Magnetic nanomaterials boost activated carbon's efficiency. Sustainable Solution: Agricultural waste-derived activated carbon is eco-friendly and cost-effective. Comprehensive Insight: Review identifies research gaps and future directions. Keywords: cobalt ion adsorption, activated carbon, agricultural waste, magnetic nanomaterials, wastewater treatment